Prospects for consumption-based growth in China - Christian Dreger; Yanqun Zhang (DIW Economic Bulletin, 2014)
The Chinese model for economic growth is undergoing a fundamental reorientation. While output has been driven by investments and exports in recent decades, private consumption is expected to become a major trigger for future GDP growth. However, the conditions for higher demand from households are far from optimal: the savings rate is high, driven in particular by the low level of social security and highly regulated financial markets. It remains to be seen whether the government can transform China into a consumer society without causing major friction.
Keywords: E02; E21; F62; P25; 330; chinese economy; savings rate; transformation and growth